Riverine nitrogen flux and its response to management, climate, and other environmental factors in Northeast and Midwest United States - Maxfield, Nicolas E.; Smith, Richard A.; Chang, Joseph; Ando, Amy W.; Lin, Tzu-Shun; Vörösmarty, Charles J.; Shih, Jhih-Shyang (Frontiers in Environmental Science, 2023)
The rate and extent of anthropogenic alteration of the global nitrogen cycle over the past four decades has been extensive, resulting in cascading negative impacts on riverine and coastal water quality. Strategies to address the sources of total nitrogen (TN) pollution must consider the overarching impact of climate change, which will play a role in physical and chemical processes involved in TN transport. Using a modified, spatially detailed SPARROW TN model, we investigated the individual effects of a set of management, technology, and policy mechanisms that alter TN pollution, based on conditions between 1980 and 2019 in the Northeast (NE) and Midwest (MW) of the United States. The largest reductions in TN pollution are related to reduction in cropland area (99 Mkg N yr-1) and atmospheric nitrogen deposition (64 Mkg N yr-1). Multi-factor experiments to suggest that increasingly efficient corn cultivars have outpaced increasing fertilizer application rate (net reduction of 8 Mkg N yr-1), while population growth has outpaced wastewater treatment (TN flux net increase of 4 Mkg N yr-1). Extreme climate scenarios suggest that persistent wet conditions increased TN flux throughout the study region. Meanwhile, persistent hot years resulted in reduced TN flux by 10 Mkg N yr-1 and 18 Mkg N yr-1 for the NE and MW respectively. The persistent dry climate scenario led to increased TN flux in the NE (6 Mkg N yr-1) and reduced TN flux in the MW (16 Mkg N yr-1). Reduced fertilizer application rate to the 1980s levels in a scenario of persistent extreme rainfall results in increased TN flux in the NE (5 Mkg N yr-1) and decreased TN flux in the MW (8 Mkg N yr-1). This finding suggests regional economic/social factors and hydrological/meteorological conditions might determine the viability of strategies to mitigate TN pollution. Finally, it is important to note the role of the ecosystem to assimilate or facilitate the processing of TN in comparison to technological interventions. We find that the potential for TN removal through aquatic decay is greatest in MW, due to the role of long travel time of rivers draining into the Lower Mississippi River.